Characterizing the performance impacts of target surface on underwater pulse laser ranging system. (November 2020) - Chen, Qi; Yam, Jian Wei; Chua, Sing Yee; Guo, Ningqun; Wang, Xin
Highlights: Analytical descriptions for target surface characteristic are thoroughly investigated and compared based on bidirectional reflection distribution function (BRDF) and laser detection and ranging (LADAR) model. According to our theoretical analysis, an underwater peak detection pulse ranging system is built to get the reflection ratio and range accuracy for different target surfaces to verify the theoretical investigation. Experimental and theoretical results show that the reflectance and accuracy depend on the surface characteristics. Our studies overcome the limitation of previous studies which focuses on improvement of system instruments performance and overcome working environment influence. Abstract: Laser-based object detection has been recognized as the most reliable technique for applications such as night vision, 3D (3-Dimensional) imaging, and especially underwater object detection. The key information is extracted from the reflected laser pulse after interacting with the target which surface directly affects the system performance. Due to the variety of the target types, it is necessary to investigate the surface characteristics and their effects on the performance of an underwater pulse laser ranging system. In this paper, the influence of target surface characteristics namely the type of materials, colors, and roughness on the reflectance and system performance are investigated through theoretical analysis using the Bidirectional Reflection Distribution Function (BRDF) and Laser Detection and Ranging (LADAR) model. An underwater peak detection pulse laser ranging system is developed to validate the results of a theoretical study. Both experimental and theoretical results clearly show that the system performance depends on the reflectance caused by the three characteristics of the target surface. This comprehensive research provides a handy reference with regards to the surface material, colors, and roughness for future improvement or correction in this domain.